The influence of competency, leadership and organizational culture mediated by job satisfaction on the performance of General Bureau Employees of the Regional Secretariat of East Nusa Tenggara Province - Bili, Maria Gradiana; Amalo, Omega Stinlly Cecilia; Man, Stanis; Djuang, Gaudensius (Manajemen dan Bisnis, 2024)
This research investigates the influence of competence, leadership and organizational culture mediated by job satisfaction on the performance of employees of the General Bureau of the Regional Secretariat of East Nusa Tenggara Province. The respondents in this research are all 106 staffs of the General Bureau. The data were collected using survey questionnaire and analysed using SEM-PLS (Structural Equation Modelling - Partial Least Squares). The results show that competence and organizational culture partially have a positive and significant effect on employee job satisfaction, but leadership has no significant effect on employee job satisfaction. Simultaneously, competence, organizational culture, leadership and job satisfaction have a positive and significant effect on the performance of employees. Further, the results of the study show that job satisfaction has a positive significant role in mediating the effect of competence and organizational culture on employee performance. However job satisfaction has no significant influence in mediating the effect of leadership on employee performance